Kualitas Buah Jeruk Siam (Citrus nobillis var microcarva L) Selama Penyimpanan Pada Berbagai Tingkat Kematangan Buah - I Kadek Riastana; Ni Komang Alit Astiari; Ni Putu Anom Sulistiawati (GEMA AGRO, 2019)
This study aims to determine the level of fruit maturity to get the quality of citrus fruits during storage. This experiment is a factorial experiment with the basic design of a simple randomized block design (RBD) one factor consisting of four levels of fruit maturity, namely: TK_1 (Physical appearance of Green fruit peels), TK_2 (Physical Display of Yellowish Green rind), TK_3 (Physical Display Yellow green rind), TK_4 (Physical Display of Evenly rind rind), each of which is repeated six times. This research was conducted in the first two places, namely in the siam plantation owned by one of the farmers in Banjar Seming, Kerta Village, Payangan District, Gianyar Regency. The second place is the Warmadewa University Faculty of Agriculture Laboratory, which runs from March to May 2017. Fruit quality seen from physical properties during storage (8th day) there was a decrease in fruit weight which was higher in physical appearance of evenly yellow rind which was 19.19 g compared to the physical appearance of yellowish green rind which was 17.26 g. Decrease in fruit diameter is also highest obtained in the physical appearance of 100% yellow rind that is 0.56 cm compared to the physical appearance of yellowish green rind that is 0.45 cm. Fruit quality seen from the chemical properties during storage (8th day) there was a decrease in vitamin C content at all levels of fruit maturity, while the total dissolved solids increased at all levels of fruit maturity. The highest total dissolved solids were obtained on the physical appearance of evenly yellow rind that was 9.42 oBrix compared to the physical appearance of greenish yellow rind, the physical appearance of yellowish green rind and the physical appearance of rind of rind, respectively 9.38 oBrix, 8 , 63 oBrix, and 8,32 oBrix. The longer the fruit is stored the more sweet the fruit is but the fruit is increasingly constricted and unfit for consumption